Geographic And Demographic Influences on The Epidemiological Patterns of Giardia Lamblia Infection in Rural Sites District Swat - Nisar, Muhammad; Khan, Fawad; Ahmad, Nisar; Saeed Ullah; Asad Ullah; Farooqi, Muhammad Waqar (Indus Journal of Bioscience Research, 2024)
This study investigates the prevalence of Giardia lamblia across different tehsils, genders, age groups, and healthcare facilities in District Swat, Pakistan. A total of 14,732 patients were analyzed, out of which 5,641 (38.3%) tested positive for Giardia lamblia. The highest tehsil-wise prevalence was observed in Babozai (59%), followed by Khwazakhela (43.1%), while Kalam recorded the lowest (10%). Gender-wise, males showed a significantly higher prevalence (59.4%) compared to females (19.3%), reflecting potential differences in exposure or susceptibility. Age group analysis indicated that children aged 0-15 years had the highest prevalence (77.3%), with infection rates decreasing in older age groups. Hospital-wise, Center Hospital in Khwazakhela reported the highest prevalence (81.3%), suggesting potential differences in diagnostic capabilities or case concentration.These findings align with global patterns of Giardia prevalence and highlight the need for targeted public health interventions, especially in high-risk areas and vulnerable groups. Enhanced water sanitation, health education, and early screening are recommended to reduce Giardia transmission. This study underscores the significance of local epidemiological data in shaping effective control strategies and improving health outcomes in endemic regions.